Synthesis and characterization of jute hybrid composites - Mediratta, Rijul (2014)
Green composites have been the topic of discussion in recent years in the research community. Their renewability and biodegradability are the key attracting factors as compared to synthetic composites. Synthetic composites are oil-derived and non-renewable. Sustainable development has been gaining increasing importance and green composites are an important factor for in achieving this ideal objective of development.